A dual‐band class A/B discrete power amplifier based on multiresonant networks. Issue 12 (22nd September 2016) - Silva, Fabrício. G. S.; de Lima, Robson N.; Freire, Raimundo C. S.
ABSTRACT: In this article, the design and implementation of a dual‐band power amplifier using multiresonant networks is presented. The measurement results have shown 50.7% and 37.2% of PAE peak efficiency at 29.6 dBm and 26.5 dBm output power, respectively, at 433 and 865 MHz. © 2016 Wiley Periodicals, Inc. Microwave Opt Technol Lett 58:2807–2811, 2016